Analisis Physical Fitnes Atlet Bolabasket Tim PON Ke XIX Sul-Sel - Anas, Nurmiana; Suwardi, Suwardi; Herman, Herman (UNIVERSITAS NEGERI MAKASSSAR, 2018)
This research aims to determine the level of physical fitnes of basketball athletes PON team XIX Sul-Sel.this study used a quantitative with descriptive percentages with data colection trough a physical component tests using tes of physical fitness that is, a test of endurance, strength, angility, explosive power, and flexibility speed. Technique of data analysis used is descriptive statistics test, linearity test and test statistics for hypothesis test by using regresion analysisis. This research is descriptive research using SPSS data procesing applicationsverse 20:00 with significant level of 95% or a 0.05. thepopulation of thhis sample is 12 male athletes and 12 female athletes, with a sampling technique using saturated sample. The results of this study study showed that: for power, male, athletes are in medium category with percentage of 41.7% and women athletes are very low category with percentage of 33.3%. for muscular endurance capability on male atheletes are in the very high catagory with perecentage of 25% and women athletes are in low category with percentage of 41.7%. for agility capabilities, male athletes are in the very high category with percentage of 66.7% and women athletes are in good category with percentage of 33.3%. for flexibility capabilities, male athletes are in the very high category with percentage 33.3%. and women athletes are in category with percentage of 33.3%. for speed capabilities, male athletes are in good category with percentage of 33.3% and women athletes are in medium category with percentage of 41.7%. for explosive power capabilities, male athletes are in good category with percentage of 25.5% and women athletes are in the best category with percentage of 41.7%. and for the common endurance capacity, male athletes are in good category with percentage of 75% and women athletes are in the very low category with percentage of 41.7%.